The International Transmission of Fisal Policy on Welfare, Investment and Trade: an Inter-temporal Approach - Gabriella Chiesa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
The remarkable increase in the real rate of interest all over the world and the appreciation of the dollar real exchange rate, toghether with the large fiscal stimulus from President Reagan's program has brought government deficits and their effects on the economy back to the foreground of the policy debate.
Keywords: 330